Stardust Interstellar Preliminary Examination IX: High‐speed interstellar dust analog capture in Stardust flight‐spare aerogel. (26th August 2014) - Postberg, F.; Hillier, J. K.; Armes, S. P.; Bugiel, S.; Butterworth, A.; Dupin, D.; Fielding, L. A.; Fujii, S.; Gainsforth, Z.; Grün, E.; Li, Y. W.; Srama, R.; et al.
Abstract The NASA Stardust mission used silica aerogel slabs to slowly decelerate and capture impinging cosmic dust particles for return to Earth. During this process, impact tracks are generated along the trajectory of the particle into the aerogel. It is believed that the morphology and dimensions of these tracks, together with the state of captured grains at track termini, may be linked to the size, velocity, and density of the impacting cosmic dust grain. Here, we present the results of laboratory hypervelocity impact experiments, during which cosmic dust analog particles (diameters of between 0.2 and 0.4 μm), composed of olivine, orthopyroxene, or an organic polymer, were accelerated onto Stardust flight‐spare low‐density (approximately 0.01 g cm−3) silica aerogel. The impact velocities (3–21 km s−1) were chosen to simulate the range of velocities expected during Stardust's interstellar dust (ISD) collection phases. Track lengths and widths, together with the success of particle capture, are analyzed as functions of impact velocity and particle composition, density, and size. Captured terminal particles from low‐density organic projectiles become undetectable at lower velocities than those from similarly sized, denser mineral particles, which are still detectable (although substantially altered by the impact process) at 15 km s−1. The survival of these terminal particles, together with the track dimensions obtained during low impact speed capture of small grains in the laboratory, indicates that two of the three best Stardust candidate extraterrestrial grains were actually captured at speeds much lower than predicted. Track length and diameters are, in general, more sensitive to impact velocities than previously expected, which makes tracks of particles with diameters of 0.4 μm and below hard to identify at low capture speeds (<10 km s−1). Therefore, although captured intact, the majority of the interstellar dust grains returned to Earth by Stardust remain to be found.